Chāngth̨ō r̨ōi čhai th̄œtthai 72 phansā : Wuthisaphā čhatphim ph̄ưa chal̄œm phrakīat Somdet Phranāng Čhao Sirikit Phrab̨ōrommarāchinī Nāt n̄ưangnai ʻōkāt phrarātchaphithī mahā mongkhon chal̄œm phrachonmaphansā 6 r̨ōp, wanthī 12 Singhākhom, Phutthasakkarāt 2547 - Son Sīmātrang (Samnakngān Lēkhāthikān Wuthi Saphā, 2005)
Description of Thai traditional hand-woven textiles; volume commemorating 72nd birth anniversary of Her Royal Highness Queen Sirikit of King Rama IX.